Penguatan Kecerdasan Spritual Peserta Didik Remaja Melalui Tilawah Al Qur’an: Studi Kasus Program One Day One Juz (ODOJ) Star - Dewi Harlina; Suswati Hendriani (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2022)
This study aims to obtain information about strengthening the spiritual intelligence of young students through Al-Qur'an recitation activities: a case study of the One Day One Juz (ODOJ) Star program. This research using a qualitative approach and case study method involved 35 informants consisting of 5 teachers as admins of the ODOJ Star group and 30 students as members of the ODOJ Star group. Research data were collected through in-depth interviews and participant observation and were processed using the Miles and Huberman model which included data collection, data reduction, data display and data verification. This study found that there were differences in attitudes related to indicators of spiritual intelligence in adolescent students between before and after participating in recitations of the Qur'an through the ODOJ Star program. Al-Qur'an recitation activities through the ODOJ Star program have been proven to be able to strengthen the spiritual intelligence of adolescent students.